The Effect of Parentting to Motivation to Learn PAI at SMPN 2 Prambon Nganjuk - Etik Eva Elvia (Didaktika Religia, 2017)
Islam requres parents to educate their children morals and values as well as to motivate them to learn. This study aims to test the theory of Eva Latipah and Hamzah B. Uno and the theory of Mangun Budiyanto by examining the influence of Mother Care Pattern towards the Motivation to learn PAI at SMPN 2 Prambon Nganjuk. Data collection techniques in this study are documentation and questionnaire. The population is all students of class VII SMPN 2 Prambon Nganjuk with the total number of 297 students. The number of samples in this study was 158 respondents, consisting of students and their mothers. The data analysis used is kendall's tau. The results of this research are: firstly, mother care pattern to her children at SMP Negeri 2 Prambon is categorized good; secondly, the motivation to learn PAI is also good; thirdly, mother care pattern does not influence the motivation to learn PAI at SMP Negeri 2 Prambon Nganjuk.